Overview of immune checkpoint inhibitor associated myocarditis mechanisms diagnostics and treatment - Feng, Shuhui; Zhao, Bingru; Sha, Shuo; Bu, Xingpeng; Zhang, Zhenzhen; Liu, Guoying; Chen, Huanzhen (Frontiers in Immunology, 2025)
Immune checkpoint inhibitor–associated myocarditis (ICI-M) has emerged as a rare yet fulminant immune-related adverse event, characterized by high mortality and diagnostic complexity. Recent studies implicate loss of immune tolerance through PD-1/PD-L1 or CTLA-4 blockade, expansion of autoreactive CD8+ T cells, cross-reactivity between tumor and cardiac antigens, and downstream inflammatory cascades as central drivers of myocardial injury. Oxidative stress, endothelial activation, and fibrotic remodeling further amplify damage. Clinically, ICI-M presents with heterogeneous symptoms ranging from subtle conduction abnormalities to fulminant cardiogenic shock. While cardiac troponins and electrocardiography offer early screening, advanced imaging—particularly cardiovascular magnetic resonance with updated Lake Louise Criteria and strain-based analysis—enables more sensitive detection. This review summarizes current insights into the immunopathogenesis, diagnostic approaches, and emerging therapeutic strategies for immune checkpoint inhibitor–associated myocarditis, highlighting the roles of autoreactive T cells, shared tumor–cardiac antigens, advanced imaging, and immunosuppressive interventions in mitigating its high morbidity and mortality.